Overview Off-label Drug Uses in Pediatric Patients at Ulinâs Hospital, Banjarmasin - Kartinah, Nani; Intannia, Difa; Fitri, Nahyanti (Indonesian Journal of Clinical Pharmacy, 2014)
Profile of off-label drug uses in Indonesia particularly in South Borneo is yet unknown. Study of off-label drug uses is necessary because its safety and effectiveness treatment for children are not guaranteed. The purpose of this study was to identify the percentage of pediatric patients who received off-label drug, the most commonly drug that used as an off-label drug, and the percentage of off-label drug based on the criteria, including: age, dose, route of administration, and indication. This research used a prospective study. The study population on this research was patients aged a month to 18 years who is treated at Ulinâs Hospital during March to May 2013. The samples of this research were patients who received antibiotics, analgesics, and antipyretics, anti-inflammatory, antihistamine, anticonvulsant, and antiemmetic drug therapy. There was 86 people (32.58%) of the 264 patients who received an off-label drug, anti-inflammatory drug was the most commonly used as an off-label drug with 38 cases (30.64 %) of the 124 cases of an off-label drug, and based on the criteria, there was 41 cases (33,06 %) off-label of age, 45 cases (36.29%) off-label of dose, no cases off-label of route of administration, and 38 cases (30,65 %) off-label of indication. Further research is needed to determine the safety and efficacy of an off-label drug.Key words: Off-label drug, pediatrics, RSUD Ulin BanjarmasinGambaran Penggunaan Obat Off-label pada Pasien Pediatrik di Rumah Sakit Ulin, BanjarmasinPenggunaan obat off-label pada anak-anak di Indonesia khususnya Kalimantan Selatan tidak diketahui. Penelitian ini diperlukan karena tidak terdapat jaminan keamanan dan efektivitas pengobatan bagi anakanak. Tujuan dari penelitian ini adalah untuk mengidentifikasi pasien anak yang mendapatkan obat offlabel, mengidentifikasi obat yang paling umum digunakan sebagai off-label, dan menentukan persentase obat off-label berdasarkan kriteria usia, dosis, cara pemberian, dan indikasi. Metode penelitian ini menggunakan prospektif studi. Populasi penelitian adalah pasien 1 bulan hingga18 tahun yang dirawat di RSUD Ulin pada bulan Maret hingga Mei 2013. Sampel penelitian adalah semua pasien usia 1 bulan hingga 18 tahun yang mendapat antibiotik, analgetik, dan antipiretik, antiinflamasi, antihistamin, antikonvulsan, dan antiemetik. Total pasien yang memperoleh obat off-label adalah 86 (32,58%) dari 264 pasien, golongan obat yang biasa digunakan off-label adalah antiinflamasi 38 (30,64%) dari 124 obat off-label. Jumlah obat off-label menurut kriteria usia adalah 41 (33,06%) dari 124 obat off-label, kriteriadosis 45 (36,29%), pada rute pemberian obat 0 (0%), dan kriteria indikasi 38 (30,65%). Diperlukan penelitian lebih lanjut untuk menentukan keamanan dan kemanjuran obat.Kata kunci: Obat off-label, pasien anak, RSUD Ulin Banjarmasin